The influence of paternal role upon father involvement among army fathers serving on active duty - Pratt, Kariga K. (Kansas State University, 2016)
Army fathers are consistently confronting and overcoming unique socio-cultural obstacles involving their paternal role. Due to the dynamic military culture in which Army fathers live, they could serve as powerful examples of resilience for all fathers in diverse communities. Transitions in the work environment such as frequent deployments, relocations, and other related stressors often create competing priorities for Army fathers. The enormous sacrifices, challenges, and demands that these dads face are often juxtaposed with the benefits, rewards, and honors involved with serving one’s country. This research examines the influence of the paternal role on father involvement among fathers currently serving on active-duty in the United States Army. Utilizing a sample of military fathers (n = 161) from an Army installation, it was possible to identify various types of paternal roles and the corresponding levels of father involvement. This study provides a comprehensive plan for support programs and services to increase father involvement within families and communities. It also serves as a basis for educational programs and services designed to support fathers in the United States armed services. The Influence of Paternal Role upon Father Involvement Model integrates conceptual underpinnings from Ecological Systems and Symbolic Interaction perspectives that were operationalized and tested in this research. This research found a positive association between paternal role and father involvement, F (₁₃, ₁₅₁) = 10.683, p < .001. It was determined that approximately 49% of the variance in paternal role could be explained by father involvement. These data revealed that paternal role has a greater impact than originally postulated in addressing issues related to competing environmental factors and father involvement. The research findings underscore the daunting socio-cultural challenges of being a tough guy and tender father through unparalleled commitment to their Nation and fatherhood displayed by soldiers serving on active duty. The implications from this investigation are broad in focus and have important ramifications for our society. Military fathers are experiencing complex issues related to father involvement and require structured comprehensive support programs. The sacrifices military fathers volunteer to take on are often more extensive than initially perceived. Therefore, dynamic fathering programs should be implemented to offset some of the challenges of unanticipated expectations and increase paternal involvement among Army fathers.
Keywords: Fathers; Father involvement; Paternal influence; Army fathers; Military dads; Paternal roles